INVESTIGATION OF STOICHIOMETRIC «AIR-FUEL» RATIO OF ORGANIC COMPOUNDS. PART 1. ALKANES - Запорожець, А. О. (Science-based technologies, 2014)
The article considered features of obtaining and applying the stoichiometric “air-fuel” ratio of organic hydrocarbons. The main objective of this work is to establish the regularities of the formation of the stoichiometric “air-fuel” ratio for the first 10 members of the alkane’s homologous series (methane, ethane, propane, butane, pentane, hexane, heptane, octane, nonane, decane). Analyzed the chemical and physical properties of alkanes, which influence on the formation of the optimal fuel mixtures. Shown the dependences of the changing of the air mass which is consumed from the excess air ratio during combustion of perfectly clean fuel materials. Shown the exact mass values of the “air-fuel” ratio for the formation of stoichiometric mixtures of alkanes. Set the fact of reducing of the needed optimal air mass for the formation of flammable mixtures under increasing of the homologous difference of alkanes. The results of investigation can be used for regulation the combustion regimes in the internal combustion engines of a car, furnaces boilers and household appliance worked on gaseous and liquid hydrocarbons (alkanes).